The effect of fluoride containing materials (mouthrinse and toothpaste) on color stability of resin composites - Ladan Ranjbar Omrani; Masumeh Hasani Tabatabaei; Soma Faridi; Elham Ahmad (Tehran University of Medical Sciences, 2017)
Background and Aims: The aim of this study was to evaluate the effects of two fluoride containing mouth rinses on the color stability of two different resin composites. Materials and Methods: 27 specimens (2×4×5 mm) were prepared from each of the following materials: a micro filled composite (Gradia, GC) and nanohybrid (Grandio). The specimens were polished by Soflex fine and superfine disks and then incubated in artificial saliva at 37°C for 24 h. The baseline color values (L, a, b) of each specimen were measured using an Easyshade spectrophotometer according to the CIELab color scale. The specimens were immersed in 20 mL of each mouth rinse and stored in an incubator at 37°C for 12 h. After incubation, the color values of all specimens were measured again, and the color change value (ΔE) was calculated. Data were analyzed by a 2-way analysis of variance at a significance level of 0.05. Results: None of the mouth rinses created clinical significant color changes in the samples. There was no statistically significant difference among color susceptibility between resin composites (P=0.330). The interaction between the effect of mouth rinses and type of restorative materials was not statistically significant (P>0.05). Conclusion: Accordance to the results of this study, the fluoride containing mouth rinses does not create color change in resin composites.